Interpersonal Relationships - Peaslee Levine, Martha (IntechOpen, 2022)
Relationships are a necessary part of life. This has always been true; community helped keep us safe as dangerous animals prowled outside our caves. We are now even more interconnected with each other. What do we know about interpersonal relationships? How do we develop the skills to connect with each other? Relationships can bring value and meaning to our lives, but, sometimes, they can have negative effects and impair our view of ourselves and others. We need to find ways to keep hope even if some relationships have scarred us. We need to recognize skills that we can use to form closer relationships in both our professional and personal lives. This book examines interpersonal relationships from many different angles. It will allow the reader to look at relationships in new ways and, perhaps, find tools to enhance and deepen connections within their lives.